Réponses

  • Utilisateur Brainly
2014-10-11T18:04:19+02:00
Ex 1 :

1/3 + 1/2 = 2/6 + 3/6 = 5/6

2/5 - 1 = 2/5 - 5/5 = - 3/5

2/3 - 4/3 x 2/5 = 2/3 - 8/15 = 10/15 - 8/15 = 2/15

(1 + 1/7) / (1 + 1/3) = (7/7 + 1/7) / (3/3 + 1/3) = 8/7 : 4/3 = 8/7 x 3/4 = 24/28 = 6/7

Ex 2 :

3x - 5 + 7x = 6 - 2x
10x + 2x = 6 + 5
12x = 11
x = 11/12

5x + 9 - 3x = 2x - 1 + x
2x - 2x - x = - 1 - 9
- x = - 10
x = 10

2(1 - 3x) + 9 - 3x = 2x - 3(2 + x)
2 - 6x + 9 - 3x = 2x - 6 - 3x
- 9x - 2x + 3x = - 6 - 2 - 9
- 8x = - 17
x = 17/8

3x + 1/2 = 5/2x - 3
3x - 5/2x = - 3 - 1/2
6/2x - 5/2x = - 6/2 - 1/2
1/2x = - 7/2
x = - 14/2
x = - 7

(3x - 1)/2 - (7x - 11)/6 = (2x + 7)/3
(3x - 1)/2 - (7x - 11)/6 - (2x + 7)/3
(9x - 3)/6 - (7x - 11)/6 - (2x + 14)/6
(- 2x - 6)/6 = 0
- (2x + 6)/6 = 0
- 2(x + 3)/6 = 0
- (x + 3)/3 = 0
Une fraction est nulle si son numérateur est nul.
x + 3 = 0
x = - 3